La Longevite Chez Les Ivoiriens - Doukoure Daouda; Kacou Fato Patrice; Coulibaly-Kone Soltié Aminata (European Scientific Journal, ESJ, 2017)
This study analyzes longevity factors among Ivoirians. Clearly, it consists on identifying the life expectancy secrets. To do this, data were gathered from religious and non-religious categories using qualitative approaches. The respondents were selected according to reasoned choice method. For this study people aged between 65 years and more were selected. Data collection took place in district of Abidjan and in the District of Odienné over a period of 3 weeks, from 06 June 2016 to 26 June 2016. Six (06) individuals were interviewed and the results revealed religious, spiritual, dietary, cultural and physical factors as the foundation of longevity among Ivoirians.